MERDEKA BELAJAR KAMPUS MERDEKA (MBKM): SARANA MEMBANGUN JARINGAN DAN KOLABORASI ANTARA MAHASISWA, DOSEN DAN MITRA - Fuadi, Tuti Marjan; Meutia, Putri Dini (Jurnal Dedikasi Pendidikan, 2024)
Research related to Merdeka Belajar Campus Merdeka has been written, but no one has focused on studying the networks and collaborations of students, lecturers and partners that emerged as a result of the implementation of Merdeka Belajar programs. This article will look at how the Independent Learning Curriculum is able to build networks and collaboration between students, lecturers and partners. The case study approach was chosen as the method in this research because it is in accordance with the scope of the research, namely only examining networks and collaboration between students, lecturers and partners that were formed through the Independent Learning policy at one tertiary institution, namely Abulyatama University. The data collection techniques used in this research are interviews, observation and documentation, which are used to obtain data from primary and secondary sources that are relevant to the social phenomenon being studied. The research results show that collaboration between students, lecturers and partners can be established through Merdeka Belajar programs (teaching campuses, internships and independent studies, student exchanges, independent entrepreneurship, even teaching practitioners). The Merdeka Belajar program has increased the frequency and intensity of collaboration between students, lecturers and partners quite high, with good quality and positive results.